Penerapan Pendidikan Inklusi di SMA Muhammadiyah 1 Padang - Nuyanita, Irhly; Novriyanti, Ernie; Putri, Miftahul Shlasya Aulia; Rahmi, Nabilatu (Arden Jaya Publisher, 2024)
This research aims to examine the implementation of inclusive education at SMA Muhammadiyah 1 Padang. Inclusive education is an educational approach that accommodates all students, including those with special needs, in the same learning environment. The research method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews, observation and document analysis. The research results show that SMA Muhammadiyah 1 Padang has taken various steps to support inclusive education, such as providing training for teachers, adapting the curriculum, and facilitating physical accessibility. However, challenges remain, especially in terms of limited resources and a lack of in-depth understanding of the needs of students with special needs. This research concludes that although there has been progress in implementing inclusive education, further efforts are needed to ensure all students receive adequate support.